RELATIVE CLAUSES AND THEIR IMPLICATIONS FOR STUDENTS’ AND TEACHERS’ GRAMMATICAL AWARENESS - Purnamasari, Asri (PEOPLE: International Journal of Social Sciences, 2020)
The use of relative clauses in English language teaching and learning is considered as a useful way for English as a Foreign Language (EFL) students and teachers to give more information about the head noun of their written or spoken sentences. It modifies a noun or noun phrase (Richards & Schmidt, 1985, p. 494). In spite of the benefits of introducing relative clauses in classroom contexts, there might be some obstacles which students and teachers face in the process of construction and relative clause use. In addition, using the relative clause needs a good understanding of their different types, the punctuation, the right pronoun and the agreement. This paper is based on literature review and will also describe and analyse a complex sentence with a relative clause. The description and analysis will be organised through sentence components analysis, different types of relative clause, the aspects of relative clause construction and use and grammatical awareness development. The purpose of this paper is to help EFL students and teachers have an overall understanding of the aspects of relative clause construction and use, and then emphasize the difficulties, which occur in the classroom context. Accordingly, through a detailed discussion of relative clauses, this paper will determine how the understanding of relative clause construction and use might develop EFL students’ and teachers’ grammatical awareness.